Resource abundance and regional development in China - Zhang, Xiaobo; Xing, Li; Fan, Shenggen; Luo, Xiaopeng (International Food Policy Research Institute, 2007)
Over the past several decades, China has made tremendous progress in market integration and infrastructure development. Demand for natural resources has increased from the booming coastal economies, causing the terms of trade to favor the resource sector, which is predominantly based in the interior regions of the country. However, the gap in economic development level between the coastal and inland regions has widened significantly. In this paper, using a panel data set at the provincial level, we show that Chinese provinces with abundant resources perform worse than their resource-poor counterparts in terms of per capita consumption growth. This trend that resource-poor areas are better off than resource-rich areas is particularly prominent in rural areas. Because of the institutional arrangements regarding property rights of natural resources, most gains from the resource boom have been captured either by the government or state owned enterprises. Thus, the windfall of natural resources has more to do with government consumption than household consumption. Moreover, in resource-rich areas, greater revenues accrued from natural resources bid up the price of non-tradable goods and hurt the competitiveness of the local economy.